Gasoline direct injection engines – A review of latest technologies and trends. Part 2. (1st April 2020) - Duronio, Francesco; De Vita, Angelo; Montanaro, Alessandro; Villante, Carlo
Highlights: Gasoline Direct Injection engines review. Mixture formation process. Combustion modelling. Emissions characterization. Injector deposits. GDCI engines. Abstract: The ever more stringent vehicle emissions rules lead gasoline engine research and development toward usage of direct injection systems. This technology is already present in commercial vehicles, but still there are many aspects that can be improved and need a deepening. For this reason, it was considered important to provide a review of the latest research topics, sorting them as if we are following the ideal fuel droplet life, beginning from the injection and ending after the combustion reaction, making available to researchers a tool to understand the state of the art of gasoline direct injection's research and technologies. In a previous work (Part 1), spray breakup, the first and crucial process that occurs when the fuel is injected within the combustion chamber, was extensively treated. In this work, a broad review of research on the mixture formation process, on combustion and on pollutants emissions is carried out.